PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID THINK ACCOUNTING (T ACCOUNT) UNTUK MENINGKATKAN PRESTASI BELAJAR PENGANTAR AKUNTANSI SISWA SMK NEGERI 1 BANYUDONO - Ekasari, Anggraeny; ., Siswandari; Octoria, Dini (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objectives of this research are to investigate the feasibility and to tested the effectiveness of product of the development of Android Think Accounting (T Account)-based learning media to improve the learning achievement in Introduction to Accounting of the students of State Vocational High School 1 of Banyudono. This research used the research and Development (R&D) method used from the ADDIE de-velopment model consisting five phases, namely: analysis; design; development; implementation; and evaluation. The subjects of the experiment were the students in Grade X Accounting 2 as the experimental class and those in Grade X Accounting 1 as the control class. The data of research were collected through questionnaire and test of learning achievement. The data of research were analyzed by using the qualita-tive data analysis; the statistical descriptive analysis; and the inferential analysis through t-test related and t-test independent. The results of research are as follows: (1) the developed Android Think Accounting (T Account)-based learning media is feasible to be used as indicated by the results of validations. The learning media expert validated it as good learning media (83.89%), the learning material expert validat-ed it as the very good learning media (88%), and the practitioner validated it as the very good learning media (94.67%); (2) the developed Android Think Accounting (T Account)-based learning media is effec-tive to improve the studentsâ learning achievement in Introduction to Accounting. Following the treatment, the studentsâ average score increased by 46 points (from the average score of 45.68 to that of 91.61), which was supported by the result of the t-test related with the p-value = 0.000 which was less than 0.05 and by that of the t-test independent with the p-value = 0.000 which was less than 0.05Keywords: Android Think Accounting (T Account)-based learning media, learning achievement, ADDIEABSTRAKTujuan penelitian ini adalah untuk mengetahui kelayakan dan menguji keefektifan produk media pembelajaran berbasis android Think Accounting (T Account) untuk meningkatkan prestasi belajar Pengantar Akuntansi siswa SMK Negeri 1 Banyudono. Penelitian ini merupakan penelitian dan pengem-bangan (research and development) yang menggunakan model pengembangan ADDIE yang meliputi tahapan: Analysis; Design; Development; Implementation; dan Evaluation. Subjek uji coba adalah kelas X Akuntansi 2 sebagai kelas tindakan dan kelas X Akuntansi 1 sebagai kelas kontrol. Instrumen pengum-pulan data yang digunakan adalah angket dan tes prestasi belajar. Teknik analisis data yang digunakan adalah analisis data kualitatif dan analisis statistik deskriptif serta analisis inferensial melalui t-test related dan t-test independent. Hasil penelitian menunjukkan bahwa: (1) media pembelajaran berbasis android Think Accounting (T Account) layak digunakan dengan rincian hasil validasi ahli media memperoleh per-sentase rata-rata 83,89%(Baik), hasil validasi ahli materi memperoleh persentase rata-rata 88%(Sangat Baik), dan hasil validasi ahli praktisi 94,67%(Sangat Baik); (2) media pembelajaran berbasis android Think Accounting (T Account) efektif untuk meningkatkan prestasi belajar Pengantar Akuntansi siswa. Ra-ta-rata prestasi belajar siswa kelas tindakan setelah penggunaan media pembelajaran meningkat sekitar 46 poin (dari 45,68 menjadi 91,61) didukung dengan hasil t-test related dengan signifikansi p<0,05 atau 0,000<0,05 dan t-test independent dengan signifikansi p<0,05 atau 0,000<0,05.Kata Kunci: media pembelajaran berbasis android Think Accounting, prestasi belajar, ADDIE.